(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article deals with the terminological system of lexical units related to bread, the interaction of language units with each other, the interrelationships between them, the essence of each unit in any system due to connections, and the relationship between units of the same system, lexical units, language units (phonemes, morphemes, lexemes, etc.) appear in speech in a specific material form, and lexical units related to bread are analyzed in terms of lexical-semantic groups in terms of synonymous, antonymic, and homonymous relationships.